Peningkatan Hasil Belajar Peserta Didik pada Pembelajaran IPAS dengan Menggunakan Model Problem Based Learning (PBL) di Kelas IV SDN 01 Sungai Jariang Kabupaten Agam - Satila, Jihan; Zuardi, Zuardi (Lembaga Yasin AlSys, 2025)
This study is motivated by the low learning outcomes of students due to the lack of active involvement in the learning process, which is still centered on the teacher. The purpose of this research is to describe the improvement in student learning outcomes in the IPAS lessons on the topic